Nepal : Second and Third Reviews Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Requests for Waiver of Performance Criteria and Extension of the Arrangement. (IMF Staff Country Reports; Country Report ;, 2006)
Major political developments have taken place in Nepal since the Executive Board concluded the Article IV Consultation in January 2006. The Koirala government is keen on early resumption of the IMF-supported program to help maintain macroeconomic stability. The international community has welcomed the peace process and has extended financial aid. Progress on structural reforms was slow owing to political uncertainties, an unsettled security environment, and inertia in policy implementation. The authorities outlined an economic program for 2006/07 consistent with Poverty Reduction Strategy Paper (PRSP)/Poverty Reduction and Growth Facility (PRGF) objectives.